Un análogo de brasinoesteroide confiere tolerancia a la sequía en soja - Perez Borroto, Lucia Sandra; Guzzo, María Carla; Posada, Gisella Anabel; Costamagna, C.; Castagnaro, A.P.; González-Olmedo, J.L.; Pardo, E.M.; Coll, Yamilet (REDBIO, 2021)
Poster